2016
DOI: 10.4081/ija.2016.712
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating strategies to improve glucosinolate concentration and root yield of field-grown horseradish in a Mediterranean environment: preliminary results

Abstract: Horseradish is grown for its enlarged taproot that is widely used as a dish condiment and as a source of horseradish peroxidase. Nowadays, the species is gaining great interest due to the richness in bioactive compounds that besides providing a high nutritional value are tested for innovative applications in different fields. Nevertheless, the effect of crop management on root yield and glucosinolates (GLS) biosynthesis is poorly documented. Aim of this study was to evaluate the root yield and GLS concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The highest yields of rhizomes were obtained at stands fertilized with ammonium sulphate (increase up to 74 %). Rivelli et al (2016) comply with the previous results; yet, they outline the importance of genetic predisposition for the AITC content in Wasabi. Manure positively influenced the content of AITC in Wasabi leaves; however, as leaves are a less used plant part, nitrogen fertilization with sulfur amendment is recommended (Sultana et al, 2002) To preserve the ITC values during storage, Sultana et al (2003b) recommend storage at temperatures -10 °C, -40 °C, -80 °C.…”
Section: Aitc Content Of Wasabisupporting
confidence: 91%
“…The highest yields of rhizomes were obtained at stands fertilized with ammonium sulphate (increase up to 74 %). Rivelli et al (2016) comply with the previous results; yet, they outline the importance of genetic predisposition for the AITC content in Wasabi. Manure positively influenced the content of AITC in Wasabi leaves; however, as leaves are a less used plant part, nitrogen fertilization with sulfur amendment is recommended (Sultana et al, 2002) To preserve the ITC values during storage, Sultana et al (2003b) recommend storage at temperatures -10 °C, -40 °C, -80 °C.…”
Section: Aitc Content Of Wasabisupporting
confidence: 91%
“…At the process of harvesting many annual roots with a diameter of 0.5-1 cm are obtained in addition to commercial product, which can be used as planting material for the following year [48]. Serbian researchers prove that the use of whole root cuttings as planting material provides for the highest yields and the highest proportion of first-class roots in the total yield as well as a stable number of planting cuttings [49][50][51][52][53][54]. If the purpose of cultivation is the intensive reproduction of planting material to increase the production of cuttings for planting, the most effective is the use of crown cuttings.…”
Section: Discussionmentioning
confidence: 99%
“…Over the threeyear study, Perlaki and Djurovka (2009) reported increases of root yields and main root weight depending on the amount and kind of fertiliser used. Large variations in root yield were also found depending on accessions; particularly, Agneta et al (2014b) comparing six horseradish accessions cultivated in temperate Mediterranean area found total root yield varying from 120 up to 1070 g plant -1 ; Rivelli et al (2016b) testing two of the six above-mentioned horseradish accessions (ST here referred as COR and MON) grown in a warm to temperate environment and supplemental irrigation reported that root FW was double in COR in comparison to MON (925 vs 476 g/plant, respectively) with diameters larger than 40%; while Rivelli et al (2016a) reported increases of both yield and glucosinulates concentration in response to fertilisation and harvesting. Considering the average values between accessions, close relationships were found relating the number of leaves both with root fresh weight (r 2 =0.88; P≤0.01) and diameter at the top (r 2 =0.82; P≤0.01) (Figure 4).…”
Section: Growingmentioning
confidence: 99%
“…Filipović et al (2015) showed a positive gross margin for organic horseradish, produced in Serbian metropolitan areas, by using the calculation of standard gross margin. Besides root yield increases, Rivelli et al (2016aRivelli et al ( , 2016b found a great increase of glucosinulates content, particularly sinigrin, in both roots and leaves, by adding nitrogen and sulphur fertilisers and by harvesting the roots of one year old during late winter for horseradish grown in a warm to temperate Mediterranean environment. According to Björkman et al (2011), the production and phytochemicals content and profile of brassicaceous crops can be significantly affected by several factors, including plant species and cultivar, agronomic conditions (developmental stage, plant organ, plant density, fertilisation, pH), season, water availability and climatic factors (mainly light and temperature).…”
Section: Introductionmentioning
confidence: 99%